Metabolomic adaptations and correlates of survival to immune checkpoint blockade - Haoxin Li (Nature Portfolio, 2019)
Immune-checkpoint inhibition therapy has achieved success in a subset of patients. Here the authors profiled about 200 relevant metabolites in patient serum samples from three independent immunotherapy trials and found the serum kynurenine/tryptophan ratio increases to be associated with worse overall survival.